The Role of Basel III in Enhancing Financial Stability Post-2008 Financial Crisis - Azamat Medetkhan (Progress in Science, 2024)
The financial crisis of 2008, originating from liquidity shortfalls and excessive risk-taking by major financial institutions, revealed profound vulnerabilities within the global financial system. This crisis, characterized by the collapse of prominent banks and the subsequent economic downturn, prompted an urgent reassessment of the regulatory framework governing the banking sector. In the wake of this financial upheaval, the Basel Committee on Banking Supervision recognized the need for a more robust regulatory standard to prevent future crises, leading to the development of Basel III. Basel III was designed to address the shortcomings exposed by the financial crisis, particularly in the areas of bank capital adequacy, risk management, and market liquidity. The reform package introduced comprehensive changes aimed at strengthening the global banking system. By raising the quality and quantity of the regulatory capital base, enhancing risk coverage, and introducing more stringent liquidity requirements, Basel III sought to increase the banking sector’s ability to absorb shocks arising from financial and economic stress. The purpose of these reforms was multifold: to fortify banks against the kind of severe financial stress that had led to the crisis, to improve risk management and governance, and to enhance the transparency and disclosures related to the banking sector’s financial health. This set of measures was not just a response to past inadequacies but a forward-looking solution intended to stabilize the financial system and protect it against future vulnerabilities. These enhancements under Basel III marked a significant shift in banking regulation, focusing not only on individual financial institutions but also on the stability of the financial system as a whole. The implementation of Basel III has been pivotal in reshaping banking practices, promoting a more cautious approach to risk, and ensuring that banks are more resilient in the face of economic fluctuations. The following sections will explore the specific reforms introduced by Basel III, their impact on bank resilience, and the overall reduction in systemic risk within the global financial landscape.